Exploring the Landscape of Coronary Artery Disease: A Comprehensive Review - Ahmad Mir, Mashooq; Altaf Dar, Mohd; Afshana Qadir (American Journal of Biomedicine and Pharmacy, 2024)
Coronary Artery Disease (CAD) remains a significant contributor to global morbidity and mortality. It is characterized by the progressive narrowing of coronary arteries due to the formation of atherosclerotic plaques, resulting in compromised blood flow to the heart muscle and ischemic events such as angina and myocardial infarction. This overview provides a succinct examination of CAD, focusing on its etiology, risk factors, clinical manifestations, and contemporary treatment modalities. The development of CAD involves a multifaceted interplay of genetic predisposition, conventional risk factors (including hypertension and dyslipidemia), and lifestyle variables. Despite its insidious onset, CAD can manifest through symptoms such as angina, dyspnea, or asymptomatic ischemia. Early detection is pivotal and can be facilitated by stress testing, coronary angiography, and non-invasive imaging techniques. Management strategies for CAD encompass lifestyle modifications, pharmacological interventions, and invasive procedures. Lifestyle adjustments entail dietary enhancements, regular physical activity, and cessation of tobacco use, all proven to attenuate CAD progression. Medications such as antiplatelets, statins, and beta-blockers target risk factors and ameliorate symptoms. Invasive interventions, including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), aim to restore coronary blood flow, thereby enhancing quality of life and augmenting survival rates. In summary, the pervasive prevalence of CAD and its clinical ramifications underscore the imperative for proactive prevention and evidence-based management. Ongoing advancements in diagnostic modalities and therapeutic strategies continue to refine CAD care, fostering optimism in combating this formidable cardiovascular ailment.